Analisis Pengaruh Financial Literasi, dan Financial Experience terhadap keputusan Investasi Saham - Hidayah, Zulfa Zakiatul; Widiastuti, Widiastuti; Mulyana, Ayang (SEIKO : Journal of Management & Business, 2024)
Investment is widely known by almost all people in Indonesia. In the current era of digitalization, investments can easily be made anywhere and at any time. Especially investments that provide quite large profits, and are quite popular with young people, namely stock investments. Stock investment is known for its high risk and high return. Even though the profits are large, we cannot deny that the risks are quite high, therefore before making investment decisions we must do research and keep our minds clear to increase the chances of investment success. The aim of this research is to determine the factors that influence investment decision making, which includes Financial Literacy and Financial experience. The data source for this research uses primary data which originates from original data by data collectors using questionnaires as a data collection technique for 100 respondents. The population and sample in this study were workers in the Cikarang industrial area. The sampling technique uses a non-probability sampling method with a purposive sampling technique with the criteria 1) Aged between 18-39 years, 2) Working in the Cikarang industrial area, 3) Interested in and already investing in the capital market. The research method uses a quantitative approach with statistical methods (2). The study carried out by researchers was to measure the positive influence of several indicators on each variable in it by using a statistical test tool with Partial Least Square (PLS) using SmartPLS software.